An industrial quality control study on Jardis Printing Corporation - Abella, Scott; Nery, Joy Erika; Ramirez, Paul; Tan, Bernice Pearl (College of Engineering, 2004)
This Industrial Quality Control study on Jardis Printing Corporation aims to apply the basic concepts and principles of Industrial Quality Control to improve the company's product and service quality. Furthermore, this study aims to perform statistical process control and process capability analysis on the data given by the Quality Management Section as well as the data gathered by the authors; specify tolerance and specification limits on the density of colors; choose and evaluate acceptance sampling plans; and make recommendations to improve the quality level of the company. Through dialogues with key personnel of the Quality Management Section as well as with the Production Manager, the group was able to identify important problems that need corrective actions. After having these problems verified, the group came to a conclusion that the major problems of the company are the large number of defectives from the Offset Printing Process, and lack of an organized quality system. In addition, other problems that were identified to have led to the large number of defectives were insufficient lighting, and poor location of the Quality Assurance Area. Based on historical data, the company averages at having 8.25 percent of the total number of units worked per job that is defective. At a unit cost of Php 2.16 per sheet and an average of 100,000 sheets per job, the losses incurred total to an amount of Php21,600 per job. Moreover, it is only in the past few months that the company has implemented the in-process quality inspection. Included here is the inefficiency of the forms used by the Quality Assurance Team and the oversimplification of control limits employed. In addition, there is no standardized procedure for outgoing inspection. Upon analyses of the problems, several recommendations were generated. For the insufficient lighting level, installation of nine new additional fluorescent lamps with diffusers, switches, and electric wires can be estimated to be Php14,570. And, with a loss of Php21,600 for one job, the cost of upgrading the lighting system in the production area can already be recovered after only one job. In order to reduce the distance traveled by the Quality Control personnel from the Production Area to the Quality Control/Assurance Area, the Quality Assurance Area should be moved to the first floor near the Offsetting Section. By doing this, the time of travel of the personnel would greatly reduce from approximately 66.667 percent to 83.333 percent. Based on the Statistical Process Control and the Process Capability Analyses, the group recommends that the company uses 20 limits instead of the customary 30 limits. When 20 limits are employed, it will be easier to detect shifts in the process average or variability. In addition, no additional labor costs will be incurred because there are currently 2 to 3 operators assigned to the machine who are merely tasked to observe the production run and to adjust the machine when necessary. Installation of an on-line computerized data collection system will increase the out of control response time as well as ensure the delegation of inspection responsibilities to the operator level. With this, sampling at more frequent intervals of 10 minutes and immediate detection of shifts is made possible. Reducing the sampling interval from 30 minutes to 10 minutes will reduce the ATS from 288.9 minutes to 96.3 minutes. This shows a significant reduction in the number of sheets that will be produced prior to detecting and adjusting the settings. The total investment for this alternative will sum to Php244,000. Considering a loss of Php21,600 per job, it will only take the savings of 11.29 jobs to recover the investment. Upon implementation, it is expected that percent defective will dramatically decrease because detection time is minimized. Furthermore, the group recommends that a chain sampling plan with n=5 and i=2 be implemented. In this new plan, the 50 percent defective lot has only a 3.61 percent chance of being accepted. To address the absence of an outgoing Acceptance Sampling inspection, the group recommends that a rectifying inspection sampling plan with a sample size of 50 and an acceptance number of 3 be adopted. The Acceptance Sampling procedure is merely another check on the outgoing quality of the products. Also, the samples taken in this plan are returned to the lot after the inspection unless they are defective. Thus, sampling costs are only incurred when defective units are found.